(untitled) (REMUNOM, 2024)
Meliponines, also called stingless bees, native bees or indigenous bees, are species found abundantly in tropical and subtropical regions that live in colonies and are characterized by their stinging apparatus being atrophied. This present work aims to determine the rheological profile of Melipona fasciculata honey from the State of Pará, at different temperatures, applying appropriate statistical tests to evaluate the difference in viscosity when varying the temperature of the product. It is noted that the decrease in temperature causes the viscosity of the honey to increase, making its flow speed slower; the opposite occurs with increasing temperature, in which viscosity decreases. Therefore, it is possible to observe that the polynomial model with five terms (or 4th degree polynomial function) was the best fit, as it presented a coefficient of determination equal to 0.9998, very close to the value 1.0. From the statistical analysis, it was possible to prove that the increase in temperature does not significantly influence the viscosity of the product, which, however, can affect its sensorial aspects. Furthermore, it was possible to obtain a mathematical model that relates these two properties, making it possible to calculate this viscosity in temperature variations from 10 to 60 °C.